The Effect Of The Nursing Intervention Based On Health Promotion Model On Acute Graft-Versus - Host Disease Preventive Behaviors In Mothers Of Children Underwent Stem Cell Transplantation - เครือจันทร์ อัจราภรณ์; ชัยวัฒน์ วราภรณ์; ตรีนัย สุรศักดิ์ (Journal of The Royal Thai Army Nurses, 2018)
The purpose of this experimental research repeated measures design was to compare acute graft-versus-host disease (aGVHD) preventive behaviors in mothers of children underwent stem cell transplantation at one, two, and three weeks after discharge. Thirty-one mothers of children in Bone Marrow Transplant Unit, Ramathibodi hospital were randomly assigned to the experimental and control groups. Sixteen mothers in the control group received the usual nursing care, while 15 mothers in the experimental group received the nursing intervention based on health promotion model. This intervention promoted the mothers’ perceived benefits of aGVHD preventive behaviors and their self-efficacy, as well as reduced their perceived barriers. The aGVHD preventive behaviors in mothers of children underwent stem cell transplantation was measured by the questionnaire developed by the researcher. Its content validity index was .82 and its KR-20 was .83. Data were analyzed by descriptive statistics and repeated measures ANOVA. It was founded that mothers receiving the nursing intervention based on health promotion model performed better aGVHD preventive behaviors than mothers receiving the usual nursing care at one, two, and three weeks after discharge, at the statistical significance level of .05.